Pengaruh Tingkat Penambahan Tepung Daun Singkong dalam Ransum Komersial terhadap Performa Broiler Strain CP 707 - Risnajati, Dede (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2011)
The study aims of research Effect of the Addition of Cassava Leaf Meal in Rations Commercial to performance  and CP 707 is to determine the extent of the effect of the addition of cassava leaf meal in commercial feed to performance of broiler strains CP 707 and find out what percentage increase in the level of cassava leaf powder in ration of good performance and large Income over feed cost. The research method is an experiment using a Completely Randomized Design (CRD) with treatments of 5 different diets, commercial diet (R0), commercial diet plus 4% cassava leaf flour (R1), commercial diet plus 8% cassava leaf meal (R2), commercial diet plus 12% cassava leaf flour (R3), commercial diet plus 16% cassava leaf flour (R4). Each treatment was repeated 5 times. Variables measured were feed consumption, body weight growth, feed conversion ratio  and income over feed cost. Data were analyzed with ANOVA, if any other treatment effect followed by Duncan's Multiple Range Test. Based on experimental the additional of cassava left powder in ration of commercial influence on feed consumption, but not give effect on body  weight growth and feed conversion ratio of broiler strain CP 707, addition of cassava leaf meal 16% give support  income over feed cost large.